ACCREDITATION BENEFITS ON TEACHER EDUCATION PROGRAMS: THE CASE OF CEBU TECHNOLOGICAL UNIVERSITY SATELLITE CAMPUSES - Camello, Lynnette Matea S; Conception, Jorelyn P; Albarracin, Virginia S; Elladora, Suzette T; Dayaganon, Crysali Therese R (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 18 No. 1, 2015, 2015)
In pursuit of continuing quality in higher education, institutions are responsive in submitting themselves for accreditation. In Cebu Technological University, the teacher education programs are periodically assessed by the Accrediting Agency of Chartered Colleges and Universities in the Philippines to determine whether the educational institution programs are doing in accordance with the accepted standards. Utilizing the descriptive case study, this study was conducted to identify the benefits derived from the accreditation through a variety of approaches like documentary review, semi-structured interview, and focus group discussion with students and members of accreditation task force in the college of education. Thematic analysis revealed that accreditation has been beneficial in improving and enhancing the quality of the teacher education programs. Specifically, accreditation has given great advantage on the quality of education in terms of: 1) identified strengths and weaknesses in the implementation of the program and the school, 2) improved quality of classroom instruction, 3) improved school resources and facilities, 4) enhanced professional development of teachers, 5) increased involvement among faculty, staff, students, and stakeholders, 6) improved guidance and support, 7) enhanced level of preparedness for an accreditation, and (8) enhanced organization and management. Findings proved that accreditation positively affect the quality of education. It is therefore suggested that the institution’s academic programs must respond to the recommendations set by the accrediting body and use the process as guide for future objectives.